The interdependence between biodiversity and socioeconomic variables on a local level: Evidence for german counties - Angela Münch; Wolfgang Völkl (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
This paper explores possible interdependence of biodiversity and several socioeconomic and political factors at the county level. It is aimed at the empirical identification of direct and indirect effects between biodiversity (loss) and their theoretical major impact factors. To date, research shows that in addition to geography, agriculture is one major determinant of biodiversity status. However, the impact of regional socioeconomic structures on biodiversity should not be underestimated. Specifically, in regard to biodiversity loss, the socioeconomic structure counteracts political measures instituted to protect biodiversity and change agricultural practice.
Keywords: Q15; Q57; R14; 330; biodiversity; socioeconomic interdependence; Bavaria; Thuringia; Biodiversität; Landwirtschaftliche Bodennutzung; Naturschutz; Geographie; Schätzung; Provinz; Deutschland